Evaluation of the willingness to perform cardiopulmonary resuscitation (CPR) with automated external defibrillator (AED) among Hong Kong Chinese using the theory of planned behaviour framework: an online cross-sectional survey - Victor C W Tam; Anthony Wai Leung Kwok (BMJ Publishing Group, 2024)
Introduction Bystander cardiopulmonary resuscitation (CPR) and defibrillation by an automated external defibrillator (AED) in out-of-hospital cardiac arrest (OHCA) events were low in Hong Kong (HK). This study evaluated the willingness and associated factors of performing CPR with AED in HK using the theory of planned behaviour (TPB).Methods A total of 1449 responses from HK Chinese aged 15-64 years were collected in a cross-sectional online survey using convenience sampling on social media including Facebook, Instagram and WhatsApp. Three TPB determinants, namely attitude, subjective norm and perceived behavioural control; and perceived barriers were asked using 5-point Likert scales. Associations between each predictor and willingness to perform CPR with AED were evaluated using univariate ordinal regressions. Predictive models were constructed using hierarchical multiple ordinal regressions (MOR) to explore associated predictors and the adjusted OR (ORadj).Results There were 44.8% and 47.8% of respondents who were willing to perform CPR and use AED, respectively. Young adults aged 18-25 years demonstrated the lowest willingness to perform CPR (ORadj=0.63, 95% CI 0.42 to 0.94, p=0.023). Knowledge level was not associated with either CPR or AED willingness, thus was eliminated in backward selection in the MOR. Attitude, subjective norm and perceived behavioural control were all positively associated with both willingness (all ORadj>1.5, p<0.001), while perceived barriers were associated with CPR willingness only (ORadj=0.77, 95% CI 0.66 to 0.91, p=0.002).Conclusions Utilisation of the TPB framework in CPR and AED community education would fill the 'know-do' gap and enhance the community's willingness to perform CPR and use an AED.